2013
DOI: 10.4081/thal.2013.e6
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S Transferase Polymorphisms Influence on Iron Overload in β-Thalassemia Patients

Abstract: In patients with β-thalassemia iron overload that leads to damage to vital organs is observed. Glutathione S transferase (GST) enzymes have an antioxidant role in detoxification processes of toxic substances. This role is determined genetically. In this study, we correlated GSTT1 and GSTM1 genotypes with iron overload measured with direct and indirect non-invasive methods; in particular, we used serum ferritin and signal intensity of the magnetic resonance image (MRI) in 42 patients with β-thalassemia, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
4
9
0
Order By: Relevance
“…The null genotype in GTSM1 and GSTT1, with neither allele active, leads to lack of enzyme activity and increased sensitivity to oxidative stress (Hahn et al 2010). This genotype has a prevalence of 23-62% across the world, 30% among Caucasians and more than 50% in the Chinese (Sclafani et al 2013;Economopoulos and Sergentanis 2010). SNPs and deletions in the mentioned loci have been correlated with a decreased glutathione activity or total loss of it (Chakarov et al 2014;Elhasid et al 2010).…”
Section: Gstt1 and Gstm1 Polymorphismsmentioning
confidence: 95%
See 2 more Smart Citations
“…The null genotype in GTSM1 and GSTT1, with neither allele active, leads to lack of enzyme activity and increased sensitivity to oxidative stress (Hahn et al 2010). This genotype has a prevalence of 23-62% across the world, 30% among Caucasians and more than 50% in the Chinese (Sclafani et al 2013;Economopoulos and Sergentanis 2010). SNPs and deletions in the mentioned loci have been correlated with a decreased glutathione activity or total loss of it (Chakarov et al 2014;Elhasid et al 2010).…”
Section: Gstt1 and Gstm1 Polymorphismsmentioning
confidence: 95%
“…SNPs and deletions in the mentioned loci have been correlated with a decreased glutathione activity or total loss of it (Chakarov et al 2014;Elhasid et al 2010). These polymorphisms as well as the null genotype can play a role in tissue damage, including heart and liver, which is caused by iron overload in c-thalassemia patients (Sclafani et al 2013). …”
Section: Gstt1 and Gstm1 Polymorphismsmentioning
confidence: 97%
See 1 more Smart Citation
“…Evidence suggests that the expression level of GST is a key factor in determining the cell sensitivity in a wide spectrum towards the toxic chemicals. 74 The enzyme is coded by 16 polymorphic genes that are divided into five classes: α (GSTA), π (GSTP), μ (GSTM), θ (GSTT), ζ (GSTZ). 75 GSTM1 and GSTT1 loci are very polymorphic and the deletion of both alleles (null genotype) eliminates the role of the enzyme and enhances the vulnerability towards oxidative stress.…”
Section: Tertiary Modifier Of β Thalassemiamentioning
confidence: 99%
“…75 GSTM1 and GSTT1 loci are very polymorphic and the deletion of both alleles (null genotype) eliminates the role of the enzyme and enhances the vulnerability towards oxidative stress. 74 It was reported that GSTT1 and GSTM1 polymorphisms affect the degree of cardiac siderosis as one of the factors that causes death in Thalassemia patients. 76 A "Null" genotype of the GST genes can lead to an enhancement of susceptibility to oxidative reactions, with the result of increased risk of tumor, prostates or cardiac disorders.…”
Section: Tertiary Modifier Of β Thalassemiamentioning
confidence: 99%